178k views
5 votes
Which expressions are equivalent to 2(b + 3c)?Choose all answers that apply:3(b + 2c)B(6 + 3c) + (6 + 3c)2(6) + 2(30)

Which expressions are equivalent to 2(b + 3c)?Choose all answers that apply:3(b + 2c-example-1

1 Answer

5 votes

The expression given as:


2(b+3c)

can be expanded as follows:


2(b)+2(3c)

Thus, option C is one of the correct answers

Further, we can expand the expression as follows:


\begin{gathered} 2(b)+2(3c) \\ \Rightarrow(b+b)+(3c+3c) \end{gathered}
\begin{gathered} \Rightarrow b+b+3c+3c \\ \Rightarrow b+3c+b+3c \\ \Rightarrow(b+3c)+(b+3c) \end{gathered}

Thus, option B is one of the correct answers

User Jbpros
by
5.2k points